ADOPTION OF IMPROVED PRODUCTION TECHNOLOGIES AMONG RICE FARMERS IN WASE LOCAL GOVERNMENT AREA OF PLATEAU STATE, NIGERIA - Vihi, Samuel Keghter; Jesse, Birma; Tanko, Philip Karik; Selzing, Peter Musa; Sulaiman, Jamila Khamis (Socio-Economics/Agribusiness Department, 2024)
This study assessed adoption of improved production technologies among rice farmers’ in Wase Local Government Areas of Plateau State, Nigeria. Multistage sampling technique was used in the selection of 160 respondents for the study. Descriptive statistics, four point Likert scale and Logit regression were used to achieve the objectives of the study. Findings from the study revealed the mean age of the farmers to be 40years. Majority (67%) of the respondents were males and 91% of them married. 44% of the respondents had secondary education and a mean farming experience of 8 years. Majority (64%) of the respondents had farming as their major occupation on average farm sizes of 1.6 hectares. The mean annual income of the farmers was N 202,356. Improved rice production technologies such as appropriate time of harvesting (3.44), land preparation by tractors (3.42), recommended time of weeding (3.41), appropriate planting dates (3.25), use of herbicides (3.24), improved seed varieties (3.11), application of recommended fertilizer (3.05), nursery practice and transplanting (2.73) all had high levels of awareness and adoption respectively among the farmers. Age, educational status, farming experience, farm size, extension contact and annual income were significant determinant of adoption of improved rice production technologies. High cost of technology (69%), inadequate extension contact (61%) inadequate credit access (48%) and lack of accessibility of some technologies (28.0) were the major constraints affecting adoption of improved rice production technologies. The study recommended the subsidization of inputs (improved seeds, fertilizers and agro-chemicals) by government to reduce cost of production.